MYTHOPOETIC FOUNDATION IN WORKS OF «FANTASY» GENRE - Ekaterina Lugovaya (Гуманитарные и юридические исследования)
The article examines cultural, historic and ethno-linguistic aspects in works of «fantasy» genre, conveying images and stories of Celtic, Greek and Roman mythology.